Prostorovost, institucionalizace a kontextualita heteronormativity: studie vyjednávání neheterosexuálních identit v Česku - Michal Pitoňák (Gender a Výzkum, 2013)
The article focuses on the relationship between space and sexuality, phenomena rarely studied together in the Czech social sciences. I use heteronormativity to describe the power polarization of largely socially constructed institutionalized relations between various sexualities. These polarizations are also inherently spatial, thus geographical phenomena. First, I focus on the discussion of various theoretical standpoints linked with foundations of heteronormativity. Secondly, I critically rethink the linear view of non-heterosexual identity development and discuss non-linear alternatives of ‘passing’ and sexual ‘closetedness’. I then incorporate this into the contextual model of sexual-identity negotiation. Thirdly, I use this model for understanding the spatial dynamics of heteronormativity and connected levels of non-heterosexuals’ comfort in particular spaces. Finally, by utilizing a rarely used visual methodology conducted on a sample of 1,589 Czech non-heterosexuals I focus on measuring the ‘perceived levels of heteronormativity’ in selected spaces. Results were translated into an ‘index of presumed spatial heteronormativity’ allowing for better understanding the everyday spatial negotiations of non-heterosexual identities.